The impact of the ASEAN economic community (AEC) on oil palm producers in Thailand - Kongyong, Kanchalika (2020)
All ASEAN member states intend to establish the ASEAN Economic Community (AEC) by 2015, in order to make ASEAN a single market and production-based with the alleged purpose of making ASEAN a more dynamic and competitive region. This study aims at identifying the impacts of this single market and the production base policy of the AEC on oil palm producers in Thailand. In order to study the impacts of the AEC on oil palm producers in Thailand, we shall resort to qualitative and quantitative research methods. These methods have applied in three provinces in Southern Thailand: Surat Thani, Krabi, and Chumphon. More specifically, the negative and positive impacts of the single market and production-based policy of the AEC on oil palm producers will concern economic and social aspects, the production system, the environment, and food security. Primary data were collected using 400 semi-structured questionnaires, were using purposive and snowball selection. The analytical tool was the Analytic Hierarchy Process (AHP) containing goals, criteria, and specified impacts of the AEC on oil palm producers in Thailand. The result reveals that the economic impacts, such as an increase in investment opportunities in oil palm and employment, are the most critical positive impacts, while social impacts are the most significant negative impacts, especially prejudice in solving by the government. The preparation for entering the AEC for oil palm in Thailand should focus on increasing production and extracted oil efficiency so that that palm oil can compete with other countries. In addition, there should be cooperation with the main producing countries in ASEAN regarding the quality of standardized palm oil and palm oil-based products (ASEAN Sustainable Palm Oil: ASPO) as well as pushing the production of oil palm and palm oil in accordance with the ASPO quality standards or RSPO standards to increase trade channels outside the region; RESUMO: Todos os estados membros da ASEAN pretendem estabelecer a Comunidade Económica da ASEAN até 2015, a fim de tornar a ASEAN um mercado único e baseado na produção, com o objetivo de tornar a ASEAN uma região mais dinâmica e competitiva. Este estudo tem como objetivo identificar os impactos desse mercado único e a política de base de produção da Comunidade Económica da ASEAN (AEC) sobre os produtores de dendezeiros na Tailândia. Para estudar os impactos da Comunidade Económica da ASEAN (AEC) nos produtores de dendezeiros da Tailândia, recorreremos a métodos de pesquisa qualitativa e quantitativa. Esses métodos foram aplicados em três províncias do sul da Tailândia: Surat Thani, Krabi, e Chumphon. Mais especificamente, os impactos negativos e positivos do mercado único e da política de produção da Comunidade Económica da ASEAN (AEC) sobre os produtores de dendezeiros envolverão aspectos económicos e sociais, sistema de produção, meio ambiente e segurança alimentar. Os dados primários foram recolhidos usando 400 questionários semiestruturados, usando seleção proposital e de bola de neve. A ferramenta analítica foi o Processo de hierarquia analítica (AHP), contendo objetivos, critérios e impactos especificados da Comunidade Económica da ASEAN (AEC) nos produtores de dendezeiros na Tailândia. O resultado revela que os impactos económicos, como o aumento das oportunidades de investimento no dendezeiro e no emprego, são os impactos positivos mais críticos. Embora os impactos sociais sejam os impactos negativos mais significativos, especialmente os preconceitos na solução por parte do governo. A preparação para entrar na Comunidade Econômica da ASEAN (AEC) para o óleo de palma na Tailândia deve concentrar-se no aumento da produção e na eficiência do óleo extraído, para que o óleo de palma possa competir com outros países. Além disso, deve haver cooperação com os principais países produtores da ASEAN no que diz respeito à qualidade de produtos padronizados de óleo de palma e óleo de palma (ASEAN Sustainable Palm Oil: ASPO), além de impulsionar a produção de óleo de palma e óleo de palma de acordo com a os padrões de qualidade ASPO ou RSPO para aumentar os canais de comércio fora da região.